Synthesis and Antimicrobial Activity of Some 1,2,4-trisubstituted Imidazolinones - Shafi, P.M.; Jirovetz, Leopold; Basheer, P.A.M. (Asian Journal of Chemistry, 2010)
The titled derivatives have been synthesized by the reaction between azalactones and glycine ethyl ester and hydrolyzing the product thus obtained. The products have been characterized by IR, NMR and elemental analysis and screened for their antimicrobial activity.